Exchange rate movements and structural break on China FDI inflows - Jung Wan Lee; Tantatape Brahmasrene (Contemporary Economics, 2020)
The aim of the study is to explore the short-run and long-run dynamic relationships between exchange rate fluctuations and foreign direct investment (FDI) inflows in China. The justification is that the undertaken topic is preeminent for devising strategies to promote economic development, thus, a course that carries much at stake not only for China but also for other developing countries. Methodology used in the study consists of co-integration tests, vector error correction models, Wald tests and impulse responses. Monthly time series data from the National Bureau of Statistics of the People's Republic of China are analyzed. The main empirical results indicate that a change in exchange rates negatively affects FDI inflows in the long run while there exists no evidence of short-run dynamics and reciprocal feedback between exchange rate fluctuations and FDI inflows. Furthermore, a structural break occurs during the 2007-2009 global financial crisis shock to FDI inflows in China. In conclusions, this research expands knowledge of factors that affect FDI inflows. To generalize the results obtained from this study, recommendations for future research include studies encompassing different economies where data are available. Such research will contribute towards improving our understanding of exchange rate systems and responses in each market.
Keywords: F21; F31; G11; G18; O24; 330; exchange rates; foreign direct investment; cointegration; vector error correction; impulse responses; China